(untitled) (Journal of the Management Sciences, 2025)
Employee commitment remains a cornerstone of organisational success, particularly within academic environments where productivity and morale directly affect educational quality. In many universities, however, staff members often face limited growth opportunities, leading to career plateauing, a psychological state in which individuals perceive stagnation in their professional development. This phenomenon can hinder motivation, engagement, and long-term organisational commitment. Against this backdrop, this study examined career plateauing and employee commitment among academic staff in the University of Uyo. Specifically, the study investigated the influence of structural, job content, and personal plateauing on continuance, affective and normative commitment. A survey research design was adopted, and a structured questionnaire was administered to a sample of 288 employees.A total of 288 copies of the research instrument were distributed to selected respondents across the study population. Of these, 244 completed instruments were successfully retrieved, yielding a response rate of 84.72%. This high rate indicates strong participant engagement and enhances the reliability and generalisability of the study findings. The returned instruments were then reviewed for completeness and consistency prior to inclusion in the data analysis. The data collected were analysed using Pearson Product-Moment Correlation, and the hypotheses were tested at the 5% significance level. The findings revealed that all dimensions of career plateauing exert a significant negative influence on employee commitment, as measured by continuance, affective, and normative commitment. Based on findings, it was concluded that career plateauing negatively affects employee commitment among academic staff in the University of Uyo. Therefore, the study recommends that the University adopt proactive career development and internal mobility strategies such as clear advancement pathways, continuous skill development, and role diversification to mitigate the effects of career plateauing.